Development of experimental approach to examine U occurrence continuity over the extended area reconnoitory boreholes: Lostoin Block, West Khasi Hills district, Meghalaya (India). (October 2015) - Kukreti, B.M.; Kumar, Pramod; Sharma, G.K.
Abstract: Exploratory drilling was undertaken in the Lostoin block, West Khasi Hills district of Meghalaya based on the geological extension to the major uranium deposit in the basin. Gamma ray logging of drilled boreholes shows considerable subsurface mineralization in the block. However, environmental and exploration related challenges such as climatic, logistic, limited core drilling and poor core recovery etc. in the block severely restricted the study of uranium exploration related index parameters for the block with a high degree confidence. The present study examines these exploration related challenges and develops an integrated approach using representative sampling of reconnoitory boreholes in the block. Experimental findings validate a similar geochemically coherent nature of radio elements (K, Ra and Th) in the Lostoin block uranium hosting environment with respect to the known block of Mahadek basin and uranium enrichment is confirmed by the lower U to Th correlation index (0.268) of hosting environment. A mineralized zone investigation in the block shows parent (refers to the actual parent uranium concentration at a location and not a secondary concentration such as the daughter elements which produce the signal from a total gamma ray measurement) favoring uranium mineralization. The confidence parameters generated under the present study have implications for the assessment of the inferred category of uranium ore in the block and setting up a road map for the systematic exploration of large uranium potential occurring over extended areas in the basin amid prevailing environmental and exploratory impediments. Highlights: Examining of U occurrence continuity over the similar geological extended area. Experimental results validates similar geo-coherence of U hosting environment. Validation of U exploration related index parameters in sedimentary environment. .Implication for exploration of large U potential over the extended are in the basin.